1990
DOI: 10.1159/000276115
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelium of the Human Endolymphatic Sac: Immunohistochemical Characterization (With 1 color plate)

Abstract: A panel of monoclonal and polyclonal antibodies has been used to study the epithelium of the extraosseous part of the human endolymphatic sac (ES) by immunohistochemistry. The ES epithelium reacted with several epithelial markers such as Lu-5, different anticytokeratins, antiepithelial membrane antigen, and anticarcinoembryonic antigen. Unexpectedly, all epithelial cells also revealed a strong positive reaction for the mesenchymal marker vimentin and for S-100 protein. ‘Neuroendocrine’, a neurosecretory antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…In a previous study, we have reported the presence of secretory immunoglobulin A (IgA) in the human ES [4,5]. Immunohisto chemical findings support the assumption that the human ES, like the gut, appears to have not only resorptive and secretory, but also immunologic and paracrine functions [2,[4][5][6], The present immunohistochemical study was designed to identify cells with immuno logical functions in the extraosseous part of the human ES.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…In a previous study, we have reported the presence of secretory immunoglobulin A (IgA) in the human ES [4,5]. Immunohisto chemical findings support the assumption that the human ES, like the gut, appears to have not only resorptive and secretory, but also immunologic and paracrine functions [2,[4][5][6], The present immunohistochemical study was designed to identify cells with immuno logical functions in the extraosseous part of the human ES.…”
Section: Introductionsupporting
confidence: 56%
“…Immunohistochemical studies of the human ES have shown that the epithelium of the ES is similar to a mesothelium which has both secretory and resorptive capabilities [2], We have demonstrated the presence of IgA and secretory component within epithe lial cells and in the lumen of the human ES [4,5], These findings led to the hypothesis that the ES has similar capabilities as the gut, which secretes IgA into the lumen [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation led to the assumption that the ES represents a metabolically active part of the inner ear and prompted further investigations [9,10], Sensitive immunohistochemical techniques allow to characterize the epithelium of the human ES and its asso ciated cell populations according to the stage of differenti ation, and to detect cellular antigens that might be related to the function of this part of the inner ear.…”
Section: Introductionmentioning
confidence: 99%